2019
DOI: 10.3390/jrfm12040163
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Financial Structure in the Technology Industry: Panel Data Evidence from the New York Stock Exchange Listed Companies

Abstract: This paper aims to analyze the influencing factors on the financial structure of 51 companies listed on the New York Stock Exchange, in the technology industry, from 2005–2018. The objective is to see the impact of independent company-specific variables such as company size, tangibility of assets, growth opportunity, effective tax rate, current liquidity, depreciation, stock rotation, financial return, working capital, price to book value, price to earnings ratio, as well as the impact of governance variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 47 publications
2
16
0
1
Order By: Relevance
“…Whereas, it has significant negative impact on STLR for overall sample data. It supports the conclusion of POT (Myers & Majluf, 1984) and TOT (Myers, 1984) as well as Berkman et al (2016), and Vintila et al (2019). It signifies that firms with higher LQD manage their short-term funds requirement internally and do not rely on external financing.…”
Section: Liquiditysupporting
confidence: 78%
See 2 more Smart Citations
“…Whereas, it has significant negative impact on STLR for overall sample data. It supports the conclusion of POT (Myers & Majluf, 1984) and TOT (Myers, 1984) as well as Berkman et al (2016), and Vintila et al (2019). It signifies that firms with higher LQD manage their short-term funds requirement internally and do not rely on external financing.…”
Section: Liquiditysupporting
confidence: 78%
“…Ramli, Latan and Solovida (2019) have suggested direct impact of liquidity as higher current ratio indicates capabilities to stand against short-term financial crisis. As against this, POT and ACT signifies that greater liquidity results into less borrowings as it ensures sufficient funds and less requirement of external funds (Berkman, İskenderoğlu, Karadeniz & Ayyildiz, 2016;Vintila et al, 2019). Following the conclusion of POT and TOT, negative relationship has been predicted between liquidity and borrowings.…”
Section: Liquiditymentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the following are used as corporate governance control variables in this study: (1) the proportion of non-executive directors; (2) the proportion of female directors; and (3) the overall board size, as measured by the logarithm of the total number of directors on the firm's board. Furthermore, we include several additional firm-specific control variables which previous studies (e.g., Yousef 2019; Vintilă et al 2019;Ahmed and Bhuyan 2020;Kedzior et al 2020) have shown to play a role in capital structure decisions; these include firm size, profitability, tangibility, and growth opportunities.…”
Section: Methodsmentioning
confidence: 99%
“…Capital structure policies are among the essential part driving the orientation of decisions that fulfill several contradictory objectives which demanding stakeholders place before a financial director (Agarwal 2013). With regard to the papers concerning capital structure, Vintilă et al (2019) established that factors such as tangibility, growth, size, or liquidity have an important influence on long-term and short-term debt rates of corporations part of the technology industry and listed on the New York Stock Exchange. Furthermore, Kedzior et al (2020) concluded that liquidity, firm age, and investments in innovativeness determine capital structure of companies listed in the Warsaw Stock Exchange that are classified as high-tech firms.…”
mentioning
confidence: 99%